2018
DOI: 10.4103/sni.sni_96_18
|View full text |Cite
|
Sign up to set email alerts
|

White cord syndrome: A devastating complication of spinal decompression surgery

Abstract: Background:Reperfusion injury of the spinal cord or “white cord syndrome” refers to the sudden onset of neurological deterioration after spinal decompressive surgery. Associated magnetic resonance (MR) findings only include focal hyperintensity on T2-weighted images without any other pathological changes.Case Description:A patient with cervical stenosis secondary to metastatic tumor in the intradural and extradural compartments presented with lower limb paraparesis. She underwent an uneventful tumor excision a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 4 publications
2
31
0
Order By: Relevance
“…In the case described in the present study, signals of abnormally high intensity in the spinal cord were detected on the postoperative sagittal T2-weighted MRI scan once acute paralysis had occurred, which displayed similarities to the aforementioned cases of ‘white cord syndrome’ ( 2 , 3 , 17 , 18 ). The neurological function of the patient gradually improved with the administration of high-dose methylprednisolone therapy, according to the NASCIS-2 protocol.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…In the case described in the present study, signals of abnormally high intensity in the spinal cord were detected on the postoperative sagittal T2-weighted MRI scan once acute paralysis had occurred, which displayed similarities to the aforementioned cases of ‘white cord syndrome’ ( 2 , 3 , 17 , 18 ). The neurological function of the patient gradually improved with the administration of high-dose methylprednisolone therapy, according to the NASCIS-2 protocol.…”
Section: Discussionsupporting
confidence: 69%
“…Antwi et al ( 17 ) reported the case of ‘white cord syndrome’ in a 68-year-old male who had developed acute hemiparesis on the left side following C4-C7 posterior laminectomy decompression in 2018. Also in 2018, Vinodh et al ( 3 ) reported similar findings in a 51-year-old female who was diagnosed with a metastatic intraspinal tumor and presented with quadriplegia following posterior cervical laminectomy and fusion for tumor resection. Papaioannou et al ( 18 ) reported the case of ‘white cord syndrome’ in a 79-year old male who had undergone C4-C6 ACDF 2 years previously because of cervical spondylotic myelopathy.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…This paraplegia is reported to be mostly caused by hematoma or iatrogenic injury. However, there is paraplegia that cannot be explained by these things, which can be caused by reperfusion injury, so called 'white cord syndrome' [1]. White cord syndrome is extremely rare and search of the literature has revealed very few cases.…”
Section: Introductionmentioning
confidence: 99%